NILAI KARAKTER DALAM FILM MENCURI RADEN SALEH KARYA ANGGA DWIMAS SASONNGKO (ALTERNATIF PENGEMBANGAN BAHAN AJARA MENELAAH STRUKTUR DAN KEBAHASAAN TEKS ULASAN) - Fahrudin, Fahrudin; Munir, Sirodjul; Agustini, Rina (Diksatrasia : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the character values in the film Mencuri Raden Saleh by Angga Dwimas Sasongko and its potential as an alternative development of teaching materials to examine the structure and language of review texts. This film tells the story of Piko's life journey, and how the robbery plan to free his family from prison requires financial resources to free him. This study uses a descriptive qualitative method with literature analysis, documentation, and analysis techniques. The process aims to identify character values contained in the dialogue, characters, scenes and storyline using the theory according to Samani and Hariyanto (2013:51). The results of the study indicate that this film contains character values such as honesty, responsibility, intelligence, health and cleanliness, caring, creativity, and mutual cooperation. Based on these findings, the film Mencuri Raden Saleh can be used as alternative teaching materials that are contextual and relevant to the needs of students, especially in teaching materials to examine the structure and language of review texts. The use of popular media such as films that are hotly discussed can increase the appeal of learning and students' understanding of their analytical skills presented in the literary works watched.